Alternative Bricks Filled with Crumb Rubber for Thermal and Acoustic Performance - hasan adeli, Ahmad Taufiq; Mohd Sari, Ts. Dr. Kamarul Aini (Progress in Engineering Application and Technology, 2025)
This effort has developed a crumb rubber sand brick. This idea made use of rubber's benefits, which include its low heat conductivity, and ability to absorb sound. As a result, crumb rubber sand brick is appropriate for the creation of wall construction materials and can also lessen its environmental impact. In order to replace the sand, specimens were made and combined with varying amounts of rubber crumb. 10%,, 15%, 20%, 25% and 30% respectively. The sample crumb rubber sand brick were create using dry mix and applying vibro-compacted. The brick are formed with standard mould volume 210 x 100 x 65mm. Altenative sand brick densitiy test results show a very significant decerease which 30% replacement the density at 7 day is 935.29 and at 28 day is 876.68 follow by compressive strenght at 7 day 0.45 Mpa and at 28 day 0.74 MPa . However, the results of the water absorption test indicate that the brick with rubber  30% replacement have increasing water absorption capacity which 18.86% compare to control. In addition, sound absorption  show at low frequency 30% repacement SAC is 0.68 and thermal conductivity test show 30% replacement K value is 0.06 W/mc˚. To maintain the physical properties which requiered strength for non-load bearing, the crumb rubber used to place sand shall not axceed 10%.